2018
DOI: 10.1016/j.watres.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of colloidal silica involved fouling behavior in three membrane distillation configurations using PTFE membrane

Abstract: Colloidal silica involved fouling behaviors in direct contact membrane distillation (DCMD), vacuum membrane distillation (VMD) and sweeping gas membrane distillation (SGMD) were studied. Three foulants were used in the experiments, including colloidal silica as representative of particulate foulants, calcium bicarbonate as dissolved inorganic foulant, and NOM (humic acid + alginate + BSA) as the dissolved organic foulant. The three types of fouants were combined to produce four different feed waters: silica al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…[59] with robust resistance to anti-scalants [34,60]. Silica scale was reported to block surface pores without wetting [28], however, this result was challenged by other reports [61][62][63]. [33,38,39]; Inverse solubility to temperature [21] Flux decline by pore blockage; negligible or detrimental effect on the distillate quality [25,33,41,43]; Co-precipitation with CaSO4 [52]; Precipitation inhibited by humic acid [43]; Remove readily by acid [22,26] CaSO4 Industrial, Seawater brine and groundwater…”
Section: Scalingmentioning
confidence: 99%
“…[59] with robust resistance to anti-scalants [34,60]. Silica scale was reported to block surface pores without wetting [28], however, this result was challenged by other reports [61][62][63]. [33,38,39]; Inverse solubility to temperature [21] Flux decline by pore blockage; negligible or detrimental effect on the distillate quality [25,33,41,43]; Co-precipitation with CaSO4 [52]; Precipitation inhibited by humic acid [43]; Remove readily by acid [22,26] CaSO4 Industrial, Seawater brine and groundwater…”
Section: Scalingmentioning
confidence: 99%
“…Among the above-listed materials, PTFE ((-C 2 F 4 -) n ) has the lowest surface energy of about 9–20·10 −3 N/m [ 119 ]. It is a highly crystalline polymer with excellent thermal and chemical resistance.…”
Section: Membranes For MDmentioning
confidence: 99%
“…Authors observed that there is a significant decrease in permeate flux at concentrations up to ~48.9 g/L. The effects of calcium carbonate in the feed solution on the permeate flux were studied by Qin et al [ 119 ]. Decomposition of calcium carbonate in VMD and SGMD was faster than in DCMD.…”
Section: Membranes For MDmentioning
confidence: 99%
“…The fouling behavior relationship between colloidal silica and three MD methods (e.g., direct contact, sweeping gas, and vacuum) was studied by Qin, Zongli, et al (2018). Three different foulant mixtures were used: silica, silica plus calcium bicarbonate, silica and NOM, and silica plus calcium bicarbonate plus NOM.…”
Section: Membrane Foulingmentioning
confidence: 99%